Procurement risk management in digital entrepreneurship and ecosystem development (DEIED) project (a World Bank funded project) - Islam, Md. Nurul (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2022.